Study on the mechanical properties and microscopic evolution mechanisms of weathered granite soil - Yizhao Wang; Ruiling Jia; Yadong Li; Kezheng Yang; Jie Cui; Yi Shan (Scientific Reports)
Abstract Studying the effects of weathering on the mechanical properties and microscopic evolution of weathered granite soil (WGS) is essential for connecting microstructure with macroscopic behavior. This study conducts systematic monotonic and cyclic triaxial tests, along with a series of microscopic tests on WGS samples, to explore the influence of weathering on WGS mechanical properties and the mechanism of granite weathering. Results indicate that both effective internal friction angle and effective cohesion decrease progressively with increased weathering. Completely weathered granite (CWG) exhibits greater dynamic strength compared to granite residual soil (GRS). Additionally, as weathering progresses, quartz fragments are lost, while feldspar and biotite weather to form secondary minerals such as kaolinite and illite, leading to an overall enrichment in aluminum and iron in the granite. Weathering causes structural deterioration of WGS. Finally, the mechanical parameters of WGS and their chemical weathering indices show a coefficient of determination ranging from 60 to 99%. This study helps elucidate the fundamental causes of performance changes in WGS, thereby optimizing engineering design and enhancing disaster prediction accuracy, while providing new research perspectives and experimental evidence for WGS.